One boy - Seeger, Laura Vaccaro (New York Roaring Brook Press, 2008)
A boy creates ten paintings in this counting book that also explores the relationship of words within words. Features die-cut pages.
"A Neal Porter Book".
Keywords: Toy and movable books -- Specimens; Vocabulary -- Fiction; Painting -- Fiction; Counting; Toy and movable books